Nickel: the last of the essential micronutrients (2011)
The knowledge about the role of Ni (Ni) in the nutrition, physiology and metabolism of the majority of crops is limited, whereas is considered to be an essential element for the higher plants starting from the 80’s of the twentieth century. The primary function of Ni in plants is defined in terms of its importance for the hydrolysis of urea; however, Ni may have an importance in other physiological processes, such as nitrogen fixation. Although the deficiencies of Ni in plants are relatively rare events, the positive response of yield and nitrogen use efficiency to applications of Ni are shown for different species. The present work summarizes the data about the essentiality of Ni and its function in plant metabolism as well as its agronomic importance for the crops.